Fractal Dimension Analysis of Mandibular Trabecular Architecture in Gingival Recession During Orthodontic Retention: A Cross-Sectional Study - Merve Küçükoğlu Çolak; Resul Çolak; Orhan Cicek (Diagnostics)
Objectives: This study used fractal dimension (FD) analysis to evaluate alveolar trabecular changes associated with gingival recessions in the mandibular incisor-canine and premolar regions in the post-orthodontic retention period, compare them to non-recession regions, and assess their correlation with plaque (PI) and gingival indices (GIs). Methods: This cross-sectional case–control study included 60 patients with mandibular gingival recession (35 females, 25 males; mean age: 21.91 ± 2.59 years), with apical trabecular bone regions of interest (ROIs) identified in the incisor-canine and premolar regions. Patients were divided into four groups based on the regions of recession, with non-recessional regions in the contralateral quadrant considered as control regions. FD analysis was performed on the specified ROIs using panoramic radiographs taken before treatment (T0), after treatment (T1), and in the retention period (T2). Patients’ PI and GI scores and incisor-mandibular plane angles (IMPAs) were recorded. Results: The FD values significantly decreased in Groups 1 and 2 (left and right incisor-canine regions) (p < 0.05), but no significant changes were found in Groups 3 and 4 (left and right premolar regions) and the control group. The FD values showed a significant correlation with the PI and GI scores (p < 0.05), but no correlation was found with IMPAs (p > 0.05). Conclusions: Alterations in alveolar trabeculation in gingival recession can be assessed by FD analysis. Decreased FD values correlate with worsening oral hygiene and higher PI and GI scores. Changes in the IMPA do not correlate with changes in FD, highlighting the importance of regular periodontal check-ups after orthodontic treatment.